GEOTEXTILE FROM PINEAPPLE LEAVES AND BIO-GROUT FOR SLOPE STABILIZATION AND EROSION CONTROL - Omar R.C.; Taha H.; Roslan R.; Baharuddin I.N.Z. (GEOMATE International Society, 2023)
Geotextiles are widely used in the civil engineering projects as ideal materials for building, road and railway constructions for separation, reinforcement, filtration, drainage, ground and pavement stabilization and soil erosion control. Geotextile made of synthetic polymeric products dominates the current market more compared to natural geotextiles due to many advantages such as the function, performance and variable applications. However, synthetic geotextiles are non-biodegradable and expensive, and may have an impact on the environment. On the contrary, natural geotextiles from plant fibers offers sustainable alternative that is safe and economical. The purpose of this study was to investigate the effectiveness of natural fibers from pineapple leaves and luffa as geotextile materials in combination with bio-grout from vegetable waste with respect to erosion control. Application of these two methods at the experimental site showed that the natural geotextile has significant influence in controlling surface erosion and reducing soil loss. These results demonstrated that the combined application of natural geotextile and bio-grout can provide an effective measure in slope protection against erosion. 2019 Int. J. of GEOMATE. All Rights Reserved.